From passion to pressure: exploring the realities of the teaching profession - Nwoko, Joy C.; Anderson, Emma; Adegboye, Oyelola A.; Malau-Aduli, Aduli E. O.; Malau-Aduli, Bunmi S. (Frontiers in Public Health, 2025)
IntroductionTeacher retention, workload, and the intention to leave the profession have become growing concerns in education, highlighting the need for a holistic approach to teacher occupational well-being.MethodsThis study employed a sequential explanatory mixed methods design to investigate factors influencing teacher well-being. A cross-sectional quantitative survey (n = 247) examined teachers’ perceptions of occupational well-being, while phenomenological qualitative interviews (n = 21) explored their workplace experiences. Using the OECD teacher occupational well-being framework, quantitative and qualitative data were integrated to identify key determinants of well-being and potential strategies for improvement.ResultsFindings revealed that teachers with strong self-efficacy and social support experienced higher job satisfaction and fewer psychosomatic symptoms, whereas increased stress levels led to greater health-related issues. Male teachers reported fewer psychosomatic symptoms than female teachers, while experienced teachers exhibited higher stress levels. Early-career teachers and junior-grade classroom teachers were more likely to consider leaving the profession, with larger class sizes contributing to greater stress and burnout. Workplace stress, student intimidation, and verbal abuse were positively associated with psychosomatic symptoms, while addressing parent or guardian concerns correlated with improved cognitive and social well-being. Lack of support was a major contributor to stress, burnout, and job dissatisfaction, whereas strong social support networks alleviated these issues.ConclusionThe study underscores the importance of ongoing leadership support and well-being-centered policies in fostering teacher occupational well-being and improving retention, particularly among early-career educators. These findings provide valuable insights for school administrators, policymakers, and educators to develop targeted strategies that create a supportive and sustainable teaching environment.